(untitled) (Journal of Naval Architecture and Marine Engineering, 2012)
This work is focused on the numerical solution of a two-dimensional, steady, incompressible electrically conducting, laminar free convection boundary layer flow of a continuously moving vertical porous plate in the presence of a transverse magnetic field and heat generation. The basic equations governing the flow are in the form of partial differential equations and have been reduced to a set of non-linear ordinary differential equations by applying suitable similarity transformations. The problem is solved numerically using shooting techniques with the forth order Runge-Kutta method. The physical behavior of different parameters for velocity, temperature and concentration has been examined graphically and analyzed quantitatively. DOI: http://dx.doi.org/10.3329/jname.v9i2.8550 Journal of Naval Architecture and Marine Engineering 9(2012) 153-167